(Table 1) Globigerinoides sacculifer oxygen and carbon isotopes at DSDP Site 68-502 - Warren L Prell (PANGAEA, 1982)
The oxygen and carbon isotopic record of G. sacculifer in DSDP Holes 502 and 502B shows that the Quaternary interval is almost complete. A slight hiatus exists in the upper Matuyama chron. The d18O data show two modes of isotopic variation: depleted values and low variability in the early Quaternary (910-1660 k.y.) and enriched composition and high variability in the late Quaternary (0-730 k.y.). These data document the change in mean composition between the early and late Quaternary, which occurs about 900 k.y. ago. These two modes of d18O variation reflect the changing ice budget on the continents and imply different envelopes of sea level variation during the early and late Quaternary. The occurrence of these two modes implies that boundary conditions during the early Quaternary were significantly different from those of the late Quaternary.
Supplement to: Prell, WL (1982): Oxygen and carbon isotope stratigraphy for the Quaternary of Hole 502B: Evidence for two modes of isotopic variability. In: Prell, WL; Gardner, JV; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 68, 455-464, https://doi.org/10.2973/dsdp.proc.68.120.1982